Fit for purpose? Validation of a conceptual framework for personal recovery with current mental health consumers. (July 2014) - Bird, Victoria; Leamy, Mary; Tew, Jerry; Le Boutillier, Clair; Williams, Julie; Slade, Mike
Objective: Mental health services in the UK, Australia and other Anglophone countries have moved towards supporting personal recovery as a primary orientation. To provide an empirically grounded foundation to identify and evaluate recovery-oriented interventions, we previously published a conceptual framework of personal recovery based on a systematic review and narrative synthesis of existing models. Our objective was to test the validity and relevance of this framework for people currently using mental health services. Method: Seven focus groups were conducted with 48 current mental health consumers in three NHS trusts across England, as part of the REFOCUS Trial. Consumers were asked about the meaning and their experience of personal recovery. Deductive and inductive thematic analysis applying a constant comparison approach was used to analyse the data. The analysis aimed to explore the validity of the categories within the conceptual framework, and to highlight any areas of difference between the conceptual framework and the themes generated from new data collected from the focus groups. Results: Both the inductive and deductive analysis broadly validated the conceptual framework, with the super-ordinate categories Connectedness, Hope and optimism, Identity, Meaning and purpose, and Empowerment (CHIME) evident in the analysis. Three areas of difference were, however, apparent in the inductive analysis. These included practical support; a greater emphasis on issues around diagnosis and medication; and scepticism surrounding recovery. Conclusions: This study suggests that the conceptual framework of personal recovery provides a defensible theoretical base for clinical and research purposes which is valid for use with current consumers. However, the three areas of difference further stress the individual nature of recovery and the need for an understanding of the population and context under investigation.